2018
DOI: 10.1002/adma.201805655
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric‐Pressure Synthesis of 2D Nitrogen‐Rich Tungsten Nitride

Abstract: increasing by the abundant WN bond. To the best of our knowledge, the experimental synthesis of 2D nitrogen-rich tungsten nitrides is not reported in literature because of the harsh synthesis condition, stemming from the sluggish reaction thermodynamics of penetrating nitrogen into tungsten lattice. [9] Overall, high pressure and temperature (P-T) synthetic method (5 GPa and 880-2570 K) was adopted to prepare various nitrogen-rich tungsten nitrides such as W 2 N 3 , W 3 N 4 . [10] However, this harsh synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 32 publications
(35 reference statements)
0
90
0
Order By: Relevance
“…Figure d shows the Fourier transform (FT) extended X‐ray adsorption fine structure (EXAFS) spectra of the W 2 N 3 and NV‐W 2 N 3 , which are obtained from normalized W L 3 ‐edge curves (Figure S4, Supporting Information). Both samples show a main coordination peak at 2.8 Å which is assigned to WW bonding . However, the intensity of the peak for NV‐W 2 N 3 at 1.8 Å (WN bonding) becomes weaker compared to that of the pristine W 2 N 3 , indicating the decreased WN bonding number.…”
Section: Exafs Curve‐fitting Results (Error Bounds (Accuracies) Were mentioning
confidence: 96%
See 2 more Smart Citations
“…Figure d shows the Fourier transform (FT) extended X‐ray adsorption fine structure (EXAFS) spectra of the W 2 N 3 and NV‐W 2 N 3 , which are obtained from normalized W L 3 ‐edge curves (Figure S4, Supporting Information). Both samples show a main coordination peak at 2.8 Å which is assigned to WW bonding . However, the intensity of the peak for NV‐W 2 N 3 at 1.8 Å (WN bonding) becomes weaker compared to that of the pristine W 2 N 3 , indicating the decreased WN bonding number.…”
Section: Exafs Curve‐fitting Results (Error Bounds (Accuracies) Were mentioning
confidence: 96%
“…2D material has onefold and fully exposed crystal surface, which is widely used as platform for both theoretical calculations and practical applications in electrocatalysis . In the meantime, many works have shown that 2D materials have surface distortion, which can endow 2D materials and their vacancies with excellent structural stability . Thus, the use of vacancy‐engineered 2D TMNs with single exposed crystal facet and stable vacancy‐site is a feasible way to construct high‐performance NRR catalysts.…”
Section: Exafs Curve‐fitting Results (Error Bounds (Accuracies) Were mentioning
confidence: 99%
See 1 more Smart Citation
“…These effective LiPSs absorbents include polar metal oxides, such as MnO 2 , TiO 2 , Nb 2 O 5 , etc. Transition metal dichalcoginde (TMDs) are also reported with excellent performance when retarding the LiPSs shuttle . Very recently, Zhou et al reported the synthesis of 2D nitrogen‐rich tungsten nitride through the atmospheric‐pressure method; The formation energy of 2D hexagonal‐W 2 N 3 (h‐W 2 N 3 ) flakes are dramatically decreased owing to the strong interaction and domain matching epitaxy between KCl and h‐W 2 N 3 .…”
Section: Methodsmentioning
confidence: 99%
“…[5] However, the development of ultrathin 2D magnetic materials, potentially important building blocks for spintronics, is still at its initial stage and only a handful of materials have the physics in ultrathin and bulk magnetic materials, and for practical applications. [18,19] This provides a viable route to obtain ultrathin flakes of a TMN with roomtemperature magnetism. This is a common issue in ultrathin 2D or 2D-like TMNs, and because of this, only a few of these materials have been reported, such as Ti 4 N 3 , [16] Mo 2 N, and V 2 N MXene, [17] MoN, [18] and W 2 N. [18] Recently, a high-yield salt-templating method for the synthesis of atomically thin TMNs by ammoniating their metal oxide counterparts was demonstrated.…”
Section: Introductionmentioning
confidence: 99%